Implicit judgments of rape cases: an experiment on the determinants and consequences of implicit evaluations in a rape case. Issue 3 (16th March 2017) - Süssenbach, Philipp; Albrecht, Svenja; Bohner, Gerd
ABSTRACT: Implicit evaluations reflect people's gut response toward an attitude object and are based on associative processes. They are the starting ground for more reflective processes and subsequent explicit evaluations. The present research examined determinants and consequences of implicit evaluations in a rape case. Situational (i.e. specifics of the rape case) and personal factors (i.e. rape myth acceptance) were demonstrated to influence both explicit and implicit judgments of the rape case. Moreover, sex of participant influenced participants' implicit evaluations but affected explicit judgments only indirectly via the implicit evaluation. People's gut response was shown to affect their explicit judgment of the case, and this effect was particularly pronounced for people with a low need for cognition (i.e. people who do not like to engage in effortful processing). The discussion focuses on the role of implicit cognition and implicit biases in judicial decision-making.